Gold Prices, World Oil Prices and Large Trade Price Index on Indonesian Sharia Stock Index with Exchange Value as A Moderating Variable in Indonesia - Fitri Fatimatuz Zahrok; Moch Sulchan; Dea Tachta Almira; Eny Agustin Nur Aeni (Cahaya Abadi Publisher, 2022)
The aim of this study was to determine how much influence the Gold Price, World Oil Price and Wholesale Price Index have on the Indonesian Sharia Stock Index with the Exchange Rate as a Moderating Variable in Indonesia. This study uses a quantitative approach to secondary data with the MRA analysis method. The results of his research show that the price of gold has a positive and significant influence on the Indonesian Islamic Stock Index; World oil prices have a positive and significant impact on the Indonesian Islamic Stock Index; Wholesale Price Index has a negative and significant influence on the Indonesian Islamic Stock Index; The rupiah exchange rate moderates (strengthens) the relationship between the gold price and the Indonesian Sharia Stock Index; The rupiah exchange rate moderates (strengthens) the relationship between world oil prices and the Indonesian Sharia Stock Index; The rupiah exchange rate moderated (strengthened) the relationship between the Wholesale Price Index and the Indonesian Sharia Stock Index.